Task composition and vocational education and training : a firm level perspective - Friedrich, Anett [Verfasser] (My University, 2021)
"In Germany, about half of the school-leavers – irrespective of their school-leaving certificate – start an apprenticeship instead of entering the labour market or university. Firms act as gatekeepers who influence which school-leavers start an apprenticeship. Previous studies have provided important information on the reasons firms train. By analysing tasks, I consider an additional characteristic that probably influences firms’ training decisions. The aim of my study is twofold: I examine whether tasks performed in a firm first correlate with the decision to provide apprenticeship training and second with the school-leaving certificate of newly hired apprentices. I use the BIBB Establishment Panel on Training and Competence Development to estimate hybrid models with the task shares of firms as the main independent variables. The results suggest that firms’ task composition affects their decisions concerning vocational education and training (VET). Firms with a high share of routine or manual tasks are more likely to be involved in VET. Moreover, high shares of manual and routine tasks are accompanied by a higher demand for apprentices with lower secondary certificates, and high shares of interactive tasks by a high demand for apprentices with the highest secondary school-leaving certificate (i.e. the Abitur)." (Autorenreferat ; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; P 2.1 Schulabgänger; 370; 330; Berufsausbildung; Ausbildungsentscheidung; Berufsentscheidung; Betrieb; Schulabschluss; Qualifikationsprofil; Tätigkeitsmerkmal; Betriebspanel